Healthy Eating: Lowering Your Blood Pressure with DASH - Valerie Weyenberg; Karla P. Shelnutt; Linda Bobroff (EDIS)
One eating plan that has been shown to prevent and reduce high blood pressure is DASH. This 3-page fact sheet is a major revision that discusses the DASH eating plan, its importance, foods included in the eating plan, and servings.